Effectively managing intractable central hyperthermia in a stroke patient by bromocriptine: a case report - Yu KW (Dove Medical Press, 2013)
Kuo-Wei Yu,1,* Yu-Hui Huang,2,3 Chien-Lin Lin,1,4,* Chang-Zern Hong,5 Li-Wei Chou1,41Department of Physical Medicine and Rehabilitation, China Medical University Hospital, Taichung, Taiwan; 2School of Medicine, Chung Shan Medical University, Taichung, Taiwan; 3Department of Physical Medicine and Rehabilitation, Chung Shan Medical University Hospital, Taichung, Taiwan; 4School of Chinese Medicine, College of Chinese Medicine, China Medical University, Taichung, Taiwan; 5Department of Physical Therapy, Hungkuang University, Taichung, Taiwan*These authors contributed equally to this workAbstract: Central hyperthermia is characterized by a rapid onset, high temperature, marked temperature fluctuation, and poor response to antipyretics and antibiotics. Although poststroke central hyperthermia is common, prolonged instances are rare. We report a case of prolonged central fever after an intracranial hemorrhage. Before the accurate diagnosis and management of central fever, the patient underwent long-term antibiotic use that led to pseudomembranous colitis. Bromocriptine was used to treat the prolonged central hyperthermia, after which the fever did not exceed 39°C. A week later, the body temperature baseline was reduced to 37°C and a low-grade fever with minor temperature fluctuation occurred only a few times. No fever occurred in the month following the treatment. After the fever subsided, the patient could undergo an aggressive rehabilitation program.Keywords: bromocriptine, central hyperthermia, fever, stroke